The Contribution of Community Singing Groups to the Well-Being of Older People: Participant Perspectives From the United Kingdom. (December 2016) - Skingley, Ann; Martin, Anne; Clift, Stephen
Current evidence suggests that participatory arts activities, and particularly group singing, may contribute to the well-being of older people. However, there is currently a paucity of prospective research from the participant perspective. This qualitative study nested within a randomized controlled trial aimed to assess participants' perspectives of the acceptability and effect on health and well-being of a community singing program for older people. Volunteers recruited to the intervention arm ( n = 131) were invited to write comments on their experiences over three data collection points of a 14-week singing program. A subsample ( n = 19) participated in a retrospective semi-structured interview. Data were subjected to content and thematic analysis. Comments and interviews from 128 individuals suggested that the singing groups led to specific, incremental benefits to physical, psychological, social, and community well-being. Benefits tended to tail off after the program ended. Suggestions were made for the future running of such groups.